Deep intronic variant in the ARSB gene as the genetic cause for Maroteaux–Lamy syndrome (MPS VI). Issue 12 (26th August 2021) - Marek‐Yagel, Dina; Eliyahu, Aviva; Veber, Alvit; Shalva, Nechama; Philosoph, Amit Mary; Barel, Ortal; Javasky, Elisheva; Pode‐Shakked, Ben; Loewenthal, Neta; Anikster, Yair; Staretz‐Chacham, Orna
Abstract: Maroteaux–Lamy syndrome (MPS‐VI) is a rare autosomal‐recessive disorder with a wide spectrum of clinical manifestations, ranging from an attenuated to a rapidly progressive disease. It is caused by variants in ARSB, which encodes the lysosomal arylsulfatase B (ARSB) enzyme, part of the degradation process of glycosaminoglycans in lysosomes. Over 220 variants have been reported so far, with a majority of missense variants. We hereby report two siblings of Bedouin origin with a diagnosis of MPS‐VI. Western blots in patient fibroblasts revealed total absence of ARSB protein production. Complete sequencing of the coding region of ARSB did not identify a candidate disease‐associated variant. However, deep sequencing of the noncoding region of ARSB by whole genome sequencing (WGS) revealed a c.1142+581A to G variant. The variant is located within intron 5 and fully segregated with the disease in the family. Determination of the genetic cause for these patients enabled targeted treatment by enzyme replacement therapy, along with appropriate genetic counseling and prenatal diagnosis for the family. These results highlight the advantage of WGS as a powerful tool, for improving the diagnostic rate of rare disease‐causing variants, and emphasize the importance of studying deep intronic sequence variation as a cause of monogenic disorders.